The Odds are Never in Their Favor: Finnick, Haymitch, and Child Commodification in The Hunger Games Series - Cenreng, Ratnasari; Destari, Herlin Putri Indah (Universitas Airlangga, 2025)
The increase in young adult speculative fiction raises the issue of child characters being treated as expendable commodities by those in power. One work in which this issue is prominent is Suzanne Collins’ The Hunger Games series. Using the conceptual definition of commodification according to Mosco’s (2009) political economy of communication theory and DeJaeghere, McCleary, and Josić’s (2016) concept of youth agency, this textual analysis on The Hunger Games series aims to understand how child commodification is represented in the side characters and how it affects their agency in adulthood. Child commodification in The Hunger Games serves two main purposes: entertainment, as seen in Finnick Odair, and government control, as seen in Haymitch Abernathy. Finnick remains a victim of commodification as an adult, which limits his agency. Meanwhile, the adult Haymitch becomes an agent of commodification, thus his agency is unrestricted.